Anchorage behavior of Fe-SMA rebars Post-Installed into concrete. (1st December 2022) - Raza, Saim; Michels, Julien; Schranz, Bernhard; Shahverdi, Moslem
Highlights: The bond behavior of Fe-SMA rebars post-installed into concrete is investigated. Investigated parameters include bond length, concrete strength, loading history etc. Comparison is made with the standard bond stress-slip relationship for steel rebars. Abstract: The unique self-prestressing behavior exhibited by Iron-based shape memory alloys (Fe-SMAs) coupled with the ease of application makes them suitable for numerous structural applications requiring post-installed reinforcement. However, the practical realization of Fe-SMA rebars as post-installed reinforcement systems entails an understanding of their bond behavior with concrete to ensure the use of adequate anchorage length for prestress transfer and prevention of premature failure. The bond behavior of cast-in-place and near-surface mounted Fe-SMA rebars with concrete has been investigated in detail in a few recent studies. However, no study has so far investigated the bond behavior of Fe-SMA rebars post-installed into concrete. To address this important knowledge gap, this paper presents an extensive experimental campaign aimed at evaluating the anchorage of post-installed Fe-SMA rebars in concrete. The experimental campaign comprised 23 specimens, with the variable parameters of the study including the bond length, state of Fe-SMA rebar (non-activated or activated), drill-hole size, strength of the adjacent concrete, type of rebar (plain, threaded, or deformed), and the type of loading history (monotonic or cyclic). The experimental results showed that for bond lengths ≥ 5db, the ribbed Fe-SMA rebars primarily fail in a pull-out failure mode and exhibit large inelastic rebar strains and load capacity at bond failure. The paper is concluded with the comparison of anchorage length predictions of conventional design models with the results of the current experimental testing campaign. The comparison demonstrates that the anchorage length recommendations of existing design standards are generally conservative for Fe-SMA rebars.